ANALISIS POLITIK TERHADAP PROSES USULAN PEMEKARAN DAERAH KABUPATEN SIMALUNGUN - Ben Adin FT; Puji Astuti; Priyatno H (Journal of Politic and Government Studies, 2016)
This writing is due to explain about how politics analysis related to the proposition of the district expansion of Simalungun, North Sumatera and factors influenced the process of expanding the District. The Method of this research is Descriptive Qualitatif. Technique of collecting data is by using direct observation to the object observed, which the researcher will do an interview to the informan related to the research being observed. Population of the Research are the Manager of Expantion Preparation Agency to District Simalungun, Special Agency of House of Representatives in District Simalungun, Component Secretary of House of Represntative in District Simalungun and Jurnalism.The Result of the Research will show that the political Process about the expansion plan, consist of some steps, such as collecting and filtering people's aspiration, designing the Agency of Expansion's Plan, Align of Agreement to the related Agency (executive and judicative) regional and central area. Furtherly, to the political dynamic and political negitiation in level of district, province and central which may effect to the delaying the District Expansion, North Sumatera. Key Word: District Expansion, Political Dynamic